2021
DOI: 10.3389/fpls.2021.743378
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Nutrient Fortified Fertilizer: A Novel Hybrid Approach for the Enrichment of Wheat Grains With Zinc

Abstract: Zinc (Zn) is a critical micronutrient that synergizes nutrient use efficiency, and improves plant growth and human health. Low Zn bioavailability in soils affects produce quality and agricultural productivity worldwide ultimately inducing deficiency in humans and animals. Zn deficiency is a leading cause of malnutrition in underdeveloped countries where a widespread population depends upon staple cereals for daily intake of calories. Modern cereal cultivars are inherently low in Zn, eventually, plants need to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The ZSB are involved in the increased bioavailability of Zn in plants through the solubilization of insoluble soil Zn fractions present in the rhizosphere. ZSB possibly increased the higher Zn availability during the grain filling stage, which increased the activity of source (flag leaf and stem) and thus more accumulation in grain (Ali et al, 2021). Kamran et al (2017) reported enhanced bioavailability of zinc and mobilized it toward wheat grains due to enhanced uptake of nutrients upon inoculation with P. fragi strain.…”
Section: Solubilization and Uptake Of Micronutrientsmentioning
confidence: 99%
“…The ZSB are involved in the increased bioavailability of Zn in plants through the solubilization of insoluble soil Zn fractions present in the rhizosphere. ZSB possibly increased the higher Zn availability during the grain filling stage, which increased the activity of source (flag leaf and stem) and thus more accumulation in grain (Ali et al, 2021). Kamran et al (2017) reported enhanced bioavailability of zinc and mobilized it toward wheat grains due to enhanced uptake of nutrients upon inoculation with P. fragi strain.…”
Section: Solubilization and Uptake Of Micronutrientsmentioning
confidence: 99%
“…Strains of zinc-solubilizing Bacillus spp. can be inoculated into the soil alone or in combination with chemical fertilizers to increase the soil zinc availability for soybean ( Sharma et al, 2012 ) and wheat ( Ali et al, 2021 ; Ramesh et al, 2014 ). It has also been suggested that seed priming or coating with zinc-soluble Bacillus is an alternative method for promoting plant development ( Bhatt & Maheshwari, 2020 ; Kushwaha et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Biologically activated zinc coated over urea (42%N;1%Zn) also known as BAZU or Zabardast Urea, is a specialty fertilizer known to increase Zn uptake in grains (Ali, 2021). Although there have been several studies for impact of nutrition on maize yield and nutrient uptake in maize grain, but there is lacking information in dynamics of potassium uptake in relation to BAZU and NPK coated with Blend Coat (N:08%; P:23%; K;18%) marketed as Zarkhez Plus.…”
Section: Introductionmentioning
confidence: 99%